Aplikasi Model Wavelet Neuro Fuzzy Untuk Memprediksi Banjir Sungai Bengawan Solo - Nurmalitasari Nurmalitasari; Sri Sumarlinda (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2018)
The objectives of this research is to implementation wavelet neuro fuzzy method to predict water level of Bengawan Solo river. The wavelet neuro fuzzy method is a model combination between discrete wavelet transformation, Artificial Neural Network (ANN) and fuzzy logic. Wavelet Neuro fuzzy modeling aims to reduce the weaknesses of each system, and combine existing advantages of each system, so the predicted result has a very small error value. Predicted when the flood is important because the predicted result can provide early warning information to the community around the river when the arrival of floods so as to reduce the risk of disaster and prepare for emergency response action. The data used in this research are high level of water level data obtained from AWLR Serenan post. The results of the wavelet neuro fuzzy method show the Mean Square error (MSE) forecast of 0.0613.